Risk Factors for Prolonged Hospital Stay after Endoscopy - Toshihiro Nishizawa; Shuntaro Yoshida; Osamu Toyoshima; Tatsuya Matsuno; Masataka Irokawa; Toru Arano; Hirotoshi Ebinuma; Hidekazu Suzuki; Takanori Kanai; Kazuhiko Koike (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The recovery room used after endoscopy has limited capacity, and an efficient flow of the endoscopy unit is desired. We investigated the duration of hospital stay after endoscopy and the risk factors for prolonged hospital stay among outpatients. Methods We retrospectively studied consecutive patients who underwent esophagogastroduodenoscopy or colonoscopy at the Toyoshima Endoscopy Clinic. We collected data on age, sex, body weight, midazolam and pethidine dosage, respiratory depression during endoscopy, and duration of hospital stay after endoscopy (scope out to check out). Risk factors for prolonged hospital stay (>100 minutes) were identified using multiple logistic regression analysis. Results We enrolled 3,898 patients, including 3,517 (90.2%) patients tested under sedation and 381 (9.8%) patients tested without sedation. Overall, 442 (11.3%) patients had prolonged stay (>100 min). The mean time difference between sedation group and non-sedation group was 44.2 minutes for esophagogastroduodenoscopy and 39.1 minutes for colonoscopy. Age (odds ratio [OR], 1.025; 95% confidence interval [CI], 1.014−1.036), female sex (OR, 1.657; 95% CI, 1.220−2.249), and midazolam dose (OR, 1.019; 95% CI, 1.013−1.026) were independently associated with prolonged hospital stay after esophagogastroduodenoscopy, with similar results for colonoscopy. Conclusions Old age, female sex, and midazolam dose were independent risk factors for prolonged hospital stay after endoscopy.